ACCOUNTING TREATMENT OF FIRE PROTECTION PRODUCT INVENTORY IN PT. REFALIA NURUL UTAMA BOGOR - Suhartono; Widiyanti, Rani (Universitas Kristen Indonesia, 2021)
Refalia Nurul Utama is a private company engaged in providing fire protection products including: Fire Extinguisher, Fire Alarm System, Fire Suppression, Water Base Fire Extinguishing System, Fire Pump with NFPA 20 standard. Supplies are always needed by every company, big or small. With inventory in a company, it is expected that the production process will run smoothly, without inventory, the company is faced with a risk that one day the company will not be able to meet consumer needs. This study uses a qualitative descriptive method, namely the method of data analysis without using statistical analysis. The data used are observation, interviews, and literature study. The results showed that PT. Refalia Nurul Utama has used the inventory recording and valuation method. In recording inventory, the perpetual method has been used, while for inventory valuation, the FIFO method has been used. Keywords: Perpetual, FIFO